IMAGE METADATA ON SOCIAL MEDIA: A COMPARATIVE STUDY ON IOS AND ANDROID APPS - Raihana Md Saidi; Muhammad Farhan Shah Bin Ahmad Rusli (Journal of Islamic, Social, Economics and Development, 2022)
Sharing and uploading photos as social media content is taking over the Internet with the advancement of mobile devices literally. Human desire to uphold and enrich these relations possibly another inspiration of the purpose of projecting onto the world. With the limitation of our hectic lives and time constraint to socialize, social media offer an easy and convenient platform to maintain contact with relatives and friends. In this paper, a comparison on how different social media handle metadata that are embedded on the photos that has been captured using mobile devices camera. When those photos are upload to the social media, all the metadata in the photos will be compare on different mobile operating systems namely Android and iOS. Some social media may remove all the metadata that are embedded in the original photos, and some may leave a little bit metadata. To extract all the metadata, a EXIF metadata extractor system is develop using Python programming language with other libraries. The result shows the image metadata that are available for the respective photos.